2011
DOI: 10.1002/ijc.25982
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CD147 is associated with prostate cancer progression

Abstract: Novel molecular markers that are associated with prostate cancer (PCa) progression will provide valuable information in the diagnosis and treatment of the disease. Extracellular matrix metalloproteinase inducer (CD147) has been demonstrated to be involved in tumor invasion, metastasis, growth and survival. In our study, we examined whether the expression of CD147 can be used as a prognostic marker for predicting PCa progression. Tissue samples from 240 patients who received radical prostatectomy for PCa were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 27 publications
5
38
1
Order By: Relevance
“…The findings of this study also confirm that, similar to the upregulation of CD147 (5,16), the increased expression of Endo180 is correlated with increasing Gleason score (Fig. 1B) and has prognostic value as an independent predictor of overall survival (Fig.…”
Section: Discussionsupporting
confidence: 82%
“…The findings of this study also confirm that, similar to the upregulation of CD147 (5,16), the increased expression of Endo180 is correlated with increasing Gleason score (Fig. 1B) and has prognostic value as an independent predictor of overall survival (Fig.…”
Section: Discussionsupporting
confidence: 82%
“…As shown in Fig. 1, both CD147 mRNA and protein were highly expressed in PCa cell lines compared to non-tumorigenic benign human prostatic epithelial cell lines (all P<0.01), which were consistent with our previous data in human PCa and non-cancerous prostate tissues (21,24,25).…”
Section: Overexpression Of Cd147 In Pca Cell Linessupporting
confidence: 91%
“…Especially in PCa, Wang et al (20) found that CD147 downregulation by RNAi technology could decrease the invasive capability of the PCa cells; data of our research group (21) and Madigan et al (22) both showed that CD147 could regulate MMPs and was involved in PCa progression. Hao et al (23) also reported that CD147 expression may be correlated with drug resistance during PCa metastasis and may be a useful potential therapeutic target in advanced disease; our research group further identified the potential role of CD147 as an independent predictor of biochemical recurrence, development of metastasis and reduced overall survival in PCa (24,25). However, the mechanisms that result in the aberrant expression of CD147 in PCa are not fully elucidated.…”
Section: Introductionmentioning
confidence: 60%
“…Tissue sections were independently evaluated by two gynecological pathologists who were blinded to the identity and clinical status of each patient. The immunohistochemical expression was semi-quantitatively measured, as described by Zhong et al (9), by assessing the percentage and staining intensity of stained tumor cells. Samples were scored from 0-3 based on the percentage of cells exhibiting positive staining as follows: 0 points, 0-5%; 1 point, 6-50%; 2 points, 51-75%; and 3 points, >75%.…”
Section: Methodsmentioning
confidence: 99%
“…MMP-2 has been extensively studied and is particularly important in cancer invasion and metastasis. Studies have shown that CD147 is overexpressed in a number of human cancer types, including gastric carcinoma, breast cancer, prostate cancer and cervical cancer (8)(9)(10), and the overexpression of CD147 is associated with an aggressive cancer phenotype and poor prognosis for the patient. Additionally, the overexpression of CD147 in malignant cells is associated with metastatic and invasive ability, and sensitivity to growth inhibitory signals (11).…”
Section: Introductionmentioning
confidence: 99%